2019
DOI: 10.1111/ctr.13684
|View full text |Cite
|
Sign up to set email alerts
|

Routine surveillance endoscopy and biopsy after isolated intestinal transplantation—Revisiting the gold standard

Abstract: The value of endoscopy and biopsy after intestinal transplantation in the absence of clinical concerns has never been investigated. We examined clinical yield of routine surveillance endoscopy and biopsy (control group, n = 28, Jan 2011 to Jun 2014).Most episodes of acute rejection were diagnosed when there were clinical symptoms or signs such as increased stoma output, fever, or bacteremia, but not by routine surveillance endoscopy and biopsy. The new protocol abandoned routine surveillance.Intestinal allogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In our series, all patients who developed stoma‐related complications had difficult abdominal wall (significantly compromised abdominal fascia layer from previous multiple surgeries), which led to imperfect stoma creation and complications. Recently the authors presented data that revealed no benefits of protocol‐driven routine surveillance E&B in the diagnosis of AR and survival 6 . We reported that the median number of E&B was 2 times and about 20% of patients did not need E&B during the first year after ITX.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In our series, all patients who developed stoma‐related complications had difficult abdominal wall (significantly compromised abdominal fascia layer from previous multiple surgeries), which led to imperfect stoma creation and complications. Recently the authors presented data that revealed no benefits of protocol‐driven routine surveillance E&B in the diagnosis of AR and survival 6 . We reported that the median number of E&B was 2 times and about 20% of patients did not need E&B during the first year after ITX.…”
Section: Discussionmentioning
confidence: 86%
“…clinical research/ practice, intestinal (allograft) function/ dysfunction, intestine/ multivisceral transplantation, patient survival, rejection: acute and adequate to monitor intestinal allografts. 6 This observation led our center to abandon protocol-driven routine surveillance E&B and establish a new protocol performing E&B only for cause following ITX. Under this new policy, number of E&B after ITX was significantly decreased to 2 times (median), and more importantly, about 20% of patients did not need E&B during the first year, a time period in which AR occurs most frequently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this practice requires validation outside of our center. 10 Patients with an ileostomy generally will not require bowel preparation, as small intestinal contents can be easily suctioned.…”
Section: P Os T Tr Ans Pl Ant Anatomy and Endoscopi C Approachmentioning
confidence: 99%
“…In total, a reduction of the number of endoscopies from 226 (historical cohort) to 57 (symptomatic cohort) was observed. Although, there were limitations regarding the sample size and the follow-up time (2014-2016) the concept is intriguing [52]. Nevertheless, the absence of a reliable biomarker and the fact that rejection might occur in asymptomatic patients makes this strategy somewhat challenging to adopt especially for smaller centres.…”
Section: Endoscopymentioning
confidence: 99%